Evaluasi Diri Madrasah (EDM) sebagai Instrumen Transformasi Digital: Peluang dan Tantangan di MI Hidayatush Shibyan Tuban - Zahrotin Nur Firda; Aliyatus Syarifah Husna; Mardiyah Mardiyah (AJER: Advanced Journal of Education and Religion, 2025)
Madrasah Self-Evaluation (EDM) is a strategic instrument to improve the quality of Islamic education. This study analyzes the urgency of preparing EDM reports at MI Hidayatush Shibyan Tuban by using case study methods and descriptive qualitative approaches. Data were collected through observations, interviews, and documentation studies. The results of the study show that EDM plays an important role in identifying the strengths, weaknesses, opportunities, and challenges of madrasas, thereby facilitating more effective planning. The implementation of EDM also increases the transparency and efficiency of madrasah management. However, obstacles such as limited human resources and infrastructure are still challenges. The conclusion of the study emphasizes that the preparation of EDM reports is very important for improving the quality of madrasah education, so it is necessary to increase the capacity of human resources and technological support to optimize its implementation.